Correction: Corrigendum: Interleukin-12 bypasses common gamma-chain signalling in emergency natural killer cell lymphopoiesis - Isabel Ohs (Nature Portfolio, 2017)
Nature Communications 8: Article number: 13708 (2016); Published: 16 Dec 2016; Updated: 4 Apr 2017 The financial support for this Article was not fully acknowledged. The acknowledgements should have included the following: The European Community FP7 grant no. 602239 (ATECT).